Cost and Equity: Decoding University Financing Reforms in Kenya - Munene, Ishmael (International Higher Education, 2024)
Recent university financing reforms in Kenya seek to mitigate the effects of neoliberalism on the financial health of public universities. The reforms introduce a new approach to public funding for universities, initiate an academic program price discrimination model, and propose a four-category student financial aid scheme. The reforms’ silence on government budgetary support for universities, implementation challenges, and institutional restructurings invite questions about long-term sustainability for the funding of public universities.